El Espíritu Santo en la teología de Santo Tomás de Aquino - Elders, Leo (Sapientia, 2015)
In recent years, it has been noted from part of specialists in St Thomas’ thought of a growing interest in his biblical commentaries. This essay is part of this movement. The author tries to draw attention of the theology of the Holy Spirit as it is presented not only in the Summa of Theology but also in other writings of the Common Doctor. After presenting a summary of the questions 27 - 36, 37 and 38 of the first part of the ST, the author shows the surprising richness of treatise on the Holy Spirit in the Summa Contra Gentiles, IV. cc. 15 to 26. The central and important role of the Holy Spirit in the life of the Church is studied in an analysis of the comment of Thomas to the Letters of St. Paul, in particular to the Romans and the Gospel of John. To emphasize the dignity of the devotion to the Holy Spirit, the author has added a section on the Gifts of the Holy Spirit, especially in its relationship with the theological and moral virtues, and charisms. A few pages on the New Law and the grace of the Holy Spirit conclude this study.